Desentralisasi Fiskal, Pertumbuhan Ekonomi Dan Pembangunan Manusia Di Sumatera - Jul Fahmi Salim; Citra Permatasari; Ade Riandar Putra (Jurnal Transformasi Administrasi, 2018)
This study aims to examine the effect of fiscal decentralization and economic growth on human development on Sumatra. The data used are regional tax data that represent fiscal decentralization, economic growth and human development index. The data used in the form of panel data of each province from 2010 to 2016. To test its influence used panel data regression model, after the best model test is a fixed effect model. The results of this study indicate that fiscal decentralization in this case local taxes have a positive and significant influence on human development on Sumatra, while economic growth has a negative but not significant effect on human development on the island of Sumatera.